Equilibrium existence in games with ties - Wojciech Olszewski; Ron Siegel (Theoretical Economics, 2023)
We provide conditions that simplify applying Reny's (1999) better-reply security to Bayesian games, and use these conditions to prove the existence of equilibria for classes of games in which payoff discontinuities arise only at "ties." These games include a general version of all-pay contests, first-prize auctions with common values, and Hotelling models with incomplete information.
Keywords: D82; D44; C72; L13; 330; better-reply security; discontinuous games; Equilibrium existence